CAVE MOTH AND BUTTERFLY FAUNA (Insecta: Lepidoptera) OF SERBIA: CURRENT STATE AND FUTURE PROSPECTS - Jakšić, Predrag (Bulletin of Natural Sciences Research, 2017)
A history of the study of Lepidoptera in caves in Serbia is given. On this basis, a comparative analysis with Lepidoptera species in neighboring countries – Croatia, Romania and Bulgaria, was carried out. The presence of cavernicolous habitats and ecological niches suitable for Lepidoptera was investigated. There is a need to investigate these groups of organisms in Serbia and it is suggested that caves in Serbia be a priority in this research.